Survival of the Fittest: The Failure to Accommodate and Compensate in the Canadian Armed Forces - Harmgardt, Julie (Canadian Labour and Employment Law Journal, 2017)
Members of the Canadian Armed Forces who are injured in the course of service are treated inequitably on two levels: first, during their military careers, by the operation of a statutory exemption that enables the CAF to sidestep the duty to accommodate disabilities, including widespread mental injuries such as PTSD; and second, following their medical release from service, by the failure to provide adequate compensation. Under the Canadian Human Rights Act, the duty to accommodate is expressly made subject to the principle of "uni- versality of service," whereby CAF members "must at all times and under any circumstances perform any functions that they may be required to perform." Universality (or the "soldier first" rule) thus provides the CAF with an auto- matic bona fide occupational requirement (BFOR) defence to discrimination claims, and permits the CAF to engage in prima facie discriminatory conduct without having to prove that it accommodated a member to the point of undue hardship. The author argues that universality cannot be justified as reasonably necessary to achieve operational objectives, having regard to staffing require- ments and level of risk, and to the fact that the CAF routinely ignores its own risk tolerance mandate by granting medical waivers. Compensation for CAF members post-release is currently provided through the New Veterans Charter. The benefits scheme created by the NVC is, in the author's view, seriously flawed: it is less generous than the predecessor legislation, excessively complex, raises unfair evidentiary burdens, and fails to ensure timely resolution of claims. The author concludes by exploring opportunities for reform, and proposes that a "presumptive" burden of proof be implemented for claimants with PTSD, similar to that which has recently been adopted in several provinces for first responders under workers' compensation legislation.